2013
DOI: 10.1037/a0033406
|View full text |Cite
|
Sign up to set email alerts
|

Relationship self-efficacy protects against mental health problems among women in bidirectionally aggressive intimate relationships with men.

Abstract: Research examining predictors or correlates of mental health problems among women who experience or use aggression in intimate relationships typically assesses factors that confer risk. Such research has primarily examined intimate partner violence (IPV) victimization or aggression frequency or severity as central risk factors for mental health problems. In the general population, one factor demonstrating a protective effect on mental health problems is self-efficacy. Research on self-efficacy among women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…These findings corroborate a previous study that supported a similar serial mediation model of self-stigma and self-efficacy in the association between prejudiced events and physical health among sexual minority populations [50]. In fact, several studies have suggested that general self-efficacy may be a source of resilience for people involved in aggressive intimate relationships [51]. Thus the results underscored the importance to increase self-efficacy, for example via personal empowerment and cognitivebehavior therapy, in order to reduce the negative impacts of IPV and stigma on mental health in counseling interventions and psycho-educational programming targeted at MSM.…”
Section: Discussionsupporting
confidence: 91%
“…These findings corroborate a previous study that supported a similar serial mediation model of self-stigma and self-efficacy in the association between prejudiced events and physical health among sexual minority populations [50]. In fact, several studies have suggested that general self-efficacy may be a source of resilience for people involved in aggressive intimate relationships [51]. Thus the results underscored the importance to increase self-efficacy, for example via personal empowerment and cognitivebehavior therapy, in order to reduce the negative impacts of IPV and stigma on mental health in counseling interventions and psycho-educational programming targeted at MSM.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown various protective factors for anxiety, such as self-efficacy ( 13 ), coping style ( 14 ), and social support ( 15 ). A positive role for physical activity in the prevention of anxiety has also been shown in several types of recent studies ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, having a positive sense of self-efficacy may protect victims of partner violence from mental health problems after partner violence. Relationship self-efficacy protected against mental health problems in a group of 354 women who were victims and perpetrators of partner violence (Sullivan, McPartland, Price, Cruza-Guet, & Swan, 2013).…”
Section: Introductionmentioning
confidence: 99%